Potret Kemampuan Sosial Peer Counselor dalam Program Training of Trainer - Puspitasari, Dwi Nikmah; Hapsari, Ayu Dyah; Multisari, Widya; An-Nisa, Lhulu (Universitas Negeri Malang, 2026)
Social skills are essential to adolescent development and support success in social, academic, and future professional contexts. This study employed the Training of Trainers (ToT) approach to enhance the social skills of peer counselors in Malang. The participants were 58 peer counselors divided into two groups: an experimental group and a control group. The ToT module was adapted from the Social Skills among Adolescents Module and had previously undergone feasibility testing. Social skills were assessed using a 23-item Social Skill Measurement instrument, which demonstrated good validity and reliability (Cronbach’s Alpha = 0.84). Paired sample t-test analysis yielded significance values of 0.071 for the control group and 0.184 for the experimental group, indicating no significant differences between pretest and posttest scores in either group. The lack of training effectiveness was influenced by several factors, particularly the pretest results, which showed that 20 participants (68.97%) were already in the high-skill category and the remaining 9 participants (31.03%) were at a moderate level, leading to a ceiling effect. Improvements are needed, including a reassessment of instrument selection, more detailed activity scheduling, the addition of ice-breaking sessions, and increased time allocation for discussion and practical exercises. AbstrakKeterampilan sosial merupakan aspek penting dalam perkembangan remaja dan berperan dalam mendukung keberhasilan di bidang sosial, akademik, serta profesional di masa depan. Pendekatan training of trainers (ToT) digunakan dalam meningkatkan keterampilan sosial konselor sebaya di Malang. Partisipan penelitian adalah 58 konselor sebaya yang dibagi ke dalam dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol. Modul ToT diadaptasi dari Social Skills among Adolescents Module dan telah melalui uji kelayakan sebelumnya. Keterampilan sosial diukur menggunakan instrumen Social Skill Measurement yang terdiri dari 23 butir, yang menunjukkan validitas dan reliabilitas yang baik dengan nilai Cronbach’s Alpha sebesar 0,84. Hasil uji paired sample t-test menghasilkan nilai signifikansi sebesar 0,071 pada kelompok kontrol dan 0,184 pada kelompok eksperimen, yang menunjukkan tidak adanya perbedaan signifikan antara skor pretest dan posttest pada kedua kelompok. Ketidakefektifan pelatihan dipengaruhi oleh beberapa faktor, terutama hasil pretest yang menunjukkan bahwa 20 partisipan (68,97%) telah berada pada kategori keterampilan tinggi, sementara 9 partisipan lainnya (31,03%) berada pada kategori sedang, sehingga menimbulkan ceiling effect. Beberapa aspek masih perlu ditingkatkan, antara lain evaluasi pemilihan instrumen, perincian jadwal kegiatan, penambahan sesi icebreaking, serta penambahan alokasi waktu untuk diskusi dan latihan praktik.